Ninety-Day Readmission Rates in a Geriatric Hip Fracture Population, From a Bundled Care Payment Initiative Perspective. Issue 12 (December 2021) - Bair, Jeffrey M.; O'Mara Gardner, Kristin; Tank, Jason C.; Georgiadis, Gregory M.; Redfern, Roberta E.
Abstract : Objective: To determine the incidence of hospital readmission in a geriatric hip fracture population within 90 days. Methods: Analysis of patients ≥60 years of age presenting with a fragility fracture of the hip from a prospective geriatric hip fracture program registry was performed. Demographics, diagnoses, treatments, complications, hospital events, and readmission for any cause within 30 and 90 days were collected. Readmission events were categorized as defined by Bundled Care Payment Initiative (BCPI)/Care for Joint Replacement payment model. Results: The population included 305 patients. All-cause readmission at 30 and 90 days was 11.5% and 19.7%, respectively. Surgical site infection or prosthesis failure accounted for 2.6% of 90 days readmissions. Application of the BCPI rules identified 44 of 60 readmitted patients (73.3%) with causes attributable to the surgical event: medical (0.7%), hospital (12.1%), and mechanical (2.6%). Death within 30 days was the largest contributor to hospital-related events. Conclusions: This study identified a 90-day readmission rate of nearly 20% in patients with geriatric fragility fractures. Application of the BCPI definitions currently used in the Care for Joint Replacement payment model will result in more readmissions being attributed to the index surgical event than classically considered. If bundled payment models remain the future, further investigation of this population's risk factors for readmission is needed in light of these findings. Level of Evidence: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.